Legal Protection of the Rights of Regional Athletes During the Post-Career Period: A Socio-Legal Study in East Kalimantan Province - Muhamad Rohadi; Rahmat Rahmat; Andi Temmassonge (Universitas Hamzanwadi, 2025)
Problems in this research: Despite being normatively guaranteed by Law Number 11 of 2022 concerning Sports, the implementation of legal protection for athletes' rights during the post-career period at the regional level still faces significant challenges. This study examines the gap between the legal framework and empirical reality in East Kalimantan Province, focusing on the effectiveness of social security and welfare for retired athletes. This study aims to analyze the implementation of legal protection for post-career athletes in East Kalimantan, identify inhibiting factors, and formulate contextual policy recommendations to strengthen the athlete social protection system. The research method uses a socio-legal approach with a qualitative case study design. Data were collected through analysis of legal documents (Law No. 11/2022, Law No. 24/2011, East Kalimantan Regional Regulation No. 5/2016), in-depth interviews with five retired athletes and eight institutional informants (Dispora, KONI, legal practitioners), and field observations. Data were analyzed thematically to integrate normative and empirical findings. The findings reveal systemic failures in implementation. The ambitious legal framework is not accompanied by operational mechanisms at the regional level. Institutional fragmentation between the Youth and Sports Agency (Dispora), the Indonesian National Sports Committee (KONI), and the Social Security Agency (BPJS) has created a vacuum of responsibility, shifting the legal rights paradigm to incidental charitable assistance. Low legal literacy among athletes and the absence of a unified database further exacerbate this situation. This study concludes that legal protection for post-career athletes in East Kalimantan remains theoretical and ineffective. Comprehensive reforms are needed, including revisions to regional regulations, the establishment of strong institutional coordination mechanisms, and legal empowerment programs for athletes to transform normative rights into accessible realities.